Populisme di Indonesia Kontemporer: Transformasi Persaingan Populisme dan Konsekuensinya dalam Dinamika Kontestasi Politik Menjelang Pemilu 2019 - Defbry Margiansyah (Jurnal Penelitian Politik, 2019)
AbstractThe rise of populism is a contemporary global phenomenon occurred in many part of the world, including Indonesia. The rising populism in the country has been epitomized by the emergence of two populist candidates, Jokowi and Prabowo, in the 2014 presidential election and recurring in the 2019 simultaneous election, which brings about new complexities in the dynamics of contemporary political contestation. The uniqueness of such competing populist politics is that both exploit the rhetoric of nationalism and social justice combined with the traits of respective candidates, in contrast to the conventional pattern of populists in other nations. This article attempts to analyze the transformation of competing populisms in two different elections and discusses its consequences to electoral politics, including the elaboration on populist’s working pattern in contestation processes and factors underlying the return of populism in Indonesia’s politics. Employing concept of populism in eclectic way and elite adjustment thesis, this paper demonstrates how populist politics is only instrumented as a vehicle of entrenched elite and oligarchic interests by pragmatically exploiting various aspects ranging from primordial identity, clientalistic relations, achievements and personalities of each candidates, instead of offering greater prospects for substantially political transformation and democratic deepening for the years to come.Keywords: Populism, Indonesia’s Election, Elite Adjusment, Identity Politics, Oligarchy, Democracy